Ο Σμύρνης Χρυσόστομος προς τον Θεσσαλονίκης Γεννάδιο. Ανέκδοτη Επιστολή του 1914 - Κιτρομηλίδης Πασχάλης Μ.; Ταχιάος Ἀντώνιος-Αἰμίλιος Ν. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2015)
The metropolitans Chrysostom of Smyrna (1910-1922) and Gennadios of Thessaloniki (1912-1951) were both Bithynians. They were born in Greek Orthodox villages in Bithynia in 1867 and 1868 respectively while their paths crossed repeatedly in their education and in their careers in the Church. They both rose to senior episcopal positions in the hierarchy of the Great Church of Christ, the Patriarchate of Constantinople, and played important roles not only as ecclesiastical but also as political leaders at the head of their respective communities in Asia Minor and in Macedonia. Their documented interaction, however, is sporadic and tends to limit itself to formalities. The letter dated April 19, 1914 from Chrysostom of Smyrna to Gennadios of Thessaloniki enriches significantly the rather sparse record of ties and communications between the two Bithynian prelates. It is addressed to Gennadios, to whom Chrysostom appeals to exercise his influence and pastoral authority among his flock in order to avert persecution of Muslims in the newly liberated territories of Northern Greece. Such actions, Chrysostom warns, may provoke reactions at the expense of Christians in Asia Minor. The occasion of the letter was an incident at the expense of the Muslims at the village of Aşıklar and their mosque in the Kilkis region north of Thessaloniki in April 1914. The letter published here is bringing the incident to the attention of historical scholarship for the first time.